Pengaruh Rasio Solvabilitas Anggaran dan Kemandirian Keuangan terhadap Financial Distress - Answella Ayu Ramadhana; Rosy Armaini; Indriani Indah Astuti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the effect of budgetary solvency ratio and financial independence on financial distress in provincial governments of Indonesia during the 2019–2023 period. This research employs a quantitative method with a sample of 34 provinces in Indonesia selected through purposive sampling based on the availability of complete budget realization reports. Data analysis was conducted using EViews version 12 through panel data regression techniques. The novelty of this research lies in its modified measurement approach, where the budgetary solvency ratio is calculated by excluding Special Allocation Funds (DAK) from revenues and adjusting capital expenditure from total expenditure. Financial distress is measured in accordance with Law Number 1 of 2022 using the proportion of capital expenditure to non-transfer regional expenditure. The results reveal that both budgetary solvency ratio and financial independence have a significant positive effect on financial distress. These findings indicate that higher budgetary solvency and financial independence increase the likelihood of financial distress in provincial governments. The study provides practical implications for local governments in maintaining accountable and stable budget structures while contributing to academic literature through an innovative measurement approach aligned with current regulations.